Education that upskills: Community service project as a critical enabler of students’ self-confidence growth - Sviatko, Martin (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this study is to elucidate how undergraduate students in Cambodia develop self-confidence through their involvement in a specific project-based learning activity. The study defines project-based learning as an academic method used by educators to provide students with meaningful, real-world learning experiences that facilitate the acquisition of essential skills and competencies. At its core, the paper focuses on a community service project, highlighting its role as a key enabler of self-confidence growth among participants. This quantitative study employs a descriptive research design and uses two surveys for data collection. Applying the convenience sampling method, the first self-administered Likert-scale questionnaire, conducted in a paper-and-pen format in May 2024, was distributed to 190 full-time university students to establish a baseline assessment of their self-confidence before the community service project. The second survey, consisting of a Likert-scale question and one open-ended question designed to gather storytelling insights, was administered to the same respondents in June 2024, shortly after the completion of the project. In addition to serving debriefing purposes, this survey formed the basis for comprehensive data analysis. To track changes in respondents’ perceptions over time and provide a single summary measure, the study utilized the mean in the Likert-scale analysis. The research findings from both surveys revealed a 14.93 percent increase in the mean self-confidence score due to the students’ involvement in project-based learning activities. Consistent with the findings of similar studies, this paper contends that a thoughtfully integrated community service project not only serves as a key enabler of self-confidence growth but also establishes a solid foundation for developing this and other emotional competencies in learners. Because this form of learning equips students with a lasting learning dividend that extends beyond their academic life and performance, the paper contributes to the ongoing pedagogical discourse on the pivotal role educational institutions play in upskilling students enrolled in undergraduate programs and other tertiary education courses. Furthermore, as relevant data stemming from similar projects in Cambodia are scarce, the study provides a window into understanding how a community service project can serve as the foundation for self-confidence growth in undergraduate students in Cambodia.